Introducing grade 10 and grade 11 learners scientific argumentation - Rikhotso, Edward Mbonjane (My University, 2019)
This report draws on Vygotsky socio-cultural and argumentation literature. The key findings of the study is that Grade 10 and 11 learners with sustained practice and support, can learn argumentation. A growing body of empirical evidence shows that the ability to engage in disciplinary specific way of thinking, talking, evaluating and articulating scientific concepts leads to development of argumentation skills (Asterham and Schwarz, 2007; Sampson and Clark, 2009; Kuhn, 1991). In light of an increasing number of what is called “progressed learners” in South African schools and in view of their poor Grade 12 academic achievements, the study sought to examine instructional strategies that can help such learners to engage more conceptually and hence help improve their performance in science. The report analyses transcripts of two Grade 11 lessons in a township school in Gauteng, South Africa, one in Physics and the other in Chemistry. An analysis of these lessons reveals the following: Firstly, learners found it easy to articulate their claims but struggled to understand the use of evidence to support these claims. The first finding is unsurprising as it has been shown from other studies locally in South Africa and abroad. Secondly, when learners began to understand the role of evidence in their arguments they were able to pick up some argumentation skills albeit at a very low level. That is, learners began to critique their peers’ arguments although in the process, revealed their own misconceptions. As in other literature this finding suggests that a sound content knowledge is a prerequisite for argumentation. The implications of this finding are that South African teacher development programs can improve students’ conceptual understanding through helping teachers to use teaching strategies that embed argument construction and justification in science.
A research report submitted to the School of Science of the University of the Witwatersrand, Johannesburg, South Africa in partial fulfilment of the Masters of Science, 2018